Application of Social Simulation Learning Model to Improve Students' Speaking and Writing Skills (Study on English Subjects in Class VII SMP N 3 Bengkulu City in the 2023/2024 academic year) - Delliani Bakri; Riyanto (CV Media Inti Teknologi, 2024)
This study aims to describe the writing and speaking abilities of seventh-grade students at SMPN 3 Bengkulu City as well as the effectiveness of applying the social simulation learning model to improve the writing and speaking abilities of seventh-grade students in English subjects at SMPN 3 Bengkulu City. The study used a quasi-experiment and classroom action research design. Twenty males and forty girls, totaling sixty pupils in the seventh grade at SMPN 3 Bengkulu City, served as the subjects of the class action research. All seventh grade pupils of SMPN 3 Bengkulu City made up the population of the experimental study. Class VII.1 (the experimental class) and class VII.2 (the control class) were the study's samples. Thirty students made up the experimental class, which included thirteen males and seventeen girls, and thirty students from the control class, which included sixteen boys and fourteen girls. The study's findings indicate that: using the social simulation learning model at SMPN 3 Bengkulu City in the 2023–2024 academic year has implications for improving students' speaking skills; using the social simulation learning model at SMPN 3 Bengkulu City in the 2023–2024 academic year has implications for improving students' writing skills; and using the social simulation model is effective for improving students' speaking and writing skills at SMPN 3 Bengkulu City in the 2023–2024 academic year because the results of the students' cognitive assessment have significantly increased.